Efficacy of dexrazoxane as a cardioprotective agent in patients receiving mitoxantrone- and daunorubicin-based chemotherapy - Lemez, P; Maresová, J (Seminars in oncology, 1998)
Dexrazoxane (DEX) selectively blocks the development of irreversible diffuse myocardial toxicity induced by anthracyclines and related antitumor agents, such as mitoxantrone (MTX). Therefore, daunorubicin (DNR) should not be administered to patients with cumulative DNR doses higher than 550 to 700 mg/m2, which we used for remission induction and consolidation therapy in patients with acute myeloid leukemia (AML). To administer further doses of anthracyclines without risks in seven relapsed AML patients and in one patient with impaired heart functions receiving consolidation therapy, we used DEX as a cardioprotective agent. Patients received DEX 30 minutes before DNR 45 mg/m2 or MTX 10 mg/m2 in doses eight to 13 times higher (DNR) or 30 to 60 times higher (MTX) in the treatment cycle with 10 high doses (2,000 mg/m2/12 hr) of cytosine arabinoside plus two doses of DNR or MTX on the fourth and fifth day. When this cycle was used as reinduction therapy, complete remission was achieved in all five cases. A cycle of MTX and etoposide was given three times with DEX as consolidation. Myelotoxicity of the treatment cycles with DEX was similar to the cycles without it. Two patients received cumulative anthracyclines doses corresponding to more than 1,300 and 1,000 mg/m2 of DNR, respectively; the remaining five relapsed patients received 550 to 850 mg/m2 of DNR, all without signs of cardiac toxicity. Delayed administration of DEX after cumulative doses of DNR 500 mg/m2 in AML patients at relapse provides cardioprotection against DNR or MTX in combination with high doses of cytosine arabinoside. This type of chemotherapy seems to be effective for remission induction in relapsed, heavily pretreated AML patients or in patients with impaired heart functions.
Keywords: mitoxantron; Heart Diseases; razoxan; nemoci srdce; Cardiovascular Agents; Middle Aged; mužské pohlaví; daunomycin; Leukemia, Myeloid, Acute; Adult; ženské pohlaví; Humans; Daunorubicin; kardiovaskulární látky; lidé středního věku; akutní myeloidní leukemie; Antineoplastic Combined Chemotherapy Protocols; Razoxane; protokoly protinádorové kombinované chemoterapie; dospělí; Female; Mitoxantrone; lidé; Male